Mechanisms of biostimulating effects of therapeutic laser in vivo. Review article - Navrátil, Leoš; Dylevský, Ivan (Sborník lékařský (1910), 1996)
The beneficial biostimulating effects induced by therapeutic laser in involved tissues was checked by a number of experimental as well as clinical works. Most of them particularly pay their attention to the description of the basic disease; there is, however, considerable imprecision in the technical characterization of the laser appliances used. Only the wave length and the power of the source are typically characterized. Further principal data are, however, missing, such as the power density, energy density, etc. These communications also suggest that their authors are not always completely familiarized with the mechanism of the stimulating action low-power laser beams in tissues. Thus, the purpose of the present communication is to summarize the existing knowledge concerning this type of treatment with considering possibilities of its use in clinical practice.
Keywords: Animals; lidé; Laser Therapy; laserová terapie; Humans; zvířata